The Effects of Chromium Histidinate on Mineral Status of Serum and Tissue in Fat-Fed and Streptozotocin-Treated Type II Diabetic Rats - Dogukan, Ayhan; Şahin, Nurhan; Tuzcu, Mehmet; Juturu, Vijaya; Orhan, Cemal; Onderci, Muhittin; Şahin, Kazım (Humana Press Inc, 2009)
The present study was conducted to investigate the effects of chromium histidinate (CrHis) against experimentally induced type II diabetes and on chromium (Cr), zinc (Zn), selenium (Se), manganese (Mn), iron (Fe), and copper (Cu) in serum, liver, and kidney of diabetic rats. The male Wistar rats (n = 60, 8 weeks old) were divided into four groups. Group I received a standard diet (12% of calories as fat); group II were fed standard diet and received CrHis (110 mcg CrHis/kg body weight per day); group III received a high-fat diet (HFD; 40% of calories as fat) for 2 weeks and then were injected with streptozotocin (STZ) on day 14 (STZ, 40 mg/kg i.p.; HFD/STZ); group IV were treated as group III (HFD/STZ) but supplemented with 110 mcg CrHis/kg body weight per day. The mineral concentrations in the serum and tissue were determined by atomic absorption spectrometry. Compared to the HFD/STZ group, CrHis significantly increased body weight and reduced blood glucose in diabetic rats (p < 0.001). Concentrations of Cr, Zn, Se, and Mn in serum, liver, and kidney of the diabetic rats were significantly lower than in the control rats (p < 0.0001). In contrast, higher Fe and Cu levels were found in serum and tissues from diabetic versus the non-diabetic rats (p < 0.001). Chromium histidinate supplementation increased serum, liver, and kidney concentrations of Cr and Zn both in diabetic and non-diabetic rats (p < 0.001). Chromium supplementation increased Mn and Se levels in diabetic rats (p < 0.001); however, it decreased Cu levels in STZ-treated group (p < 0.001). Chromium histidinate supplementation did not affect Fe levels in both groups (p > 0.05). The results of the present study conclude that supplementing Cr to the diet of diabetic rats influences serum and tissue Cr, Zn, Se, Mn, and Cu concentrations.
Keywords: Chromium histidinate; Type II diabetes mellitus; Rat; High-fat diet